The materials science of skin: Analysis, characterization, and modeling. (May 2020) - Pissarenko, Andrei; Meyers, Marc A.
Abstract: Skin is the outermost layer of the body and acts as a primary protective barrier against external agents such as heat, light, infection, and injury. Additionally, skin regulates the temperature of the body and the exchange of fluids. Skin contains a vast network of nerves, glands, and vessels that enable sensing of heat, touch, pressure and pain, and is also a crucial interface that regulates our body temperature and stores water and lipids to maintain a healthy metabolism. In order to fulfill such a broad range of functions throughout life, skin must be able to withstand and recover from significant deformation as well as mitigate tear propagation that can occur during growth, movement, and injuries affecting its integrity. Hence, characterizing the mechanical behavior of skin and understanding the underlying mechanisms of deformation at different spatial scales is essential in a large spectrum of applications such as surgery, cosmetics, forensics, biomimetics and engineering of protective gear or artificial grafts, among others. The present review draws a comprehensive list of experimental techniques that have been developed over the years to test skin's nonlinear elastic, viscoelastic, and dissipative properties. To identify parameters affecting its behavior, a significant number of models have been developed, some of which are detailed here; they range from macroscopic constitutive laws to structurally-based formulations, involving nonlinear, dynamic, or damage-inducing processes. The principal structural elements within the dermis, and especially the arrangement and orientation of the collagen fibrils and fibers, are presented; their incorporation into the constitutive models is discussed. Future challenges and perspectives in implementing more accurate structural models are highlighted. Major efforts at developing and using synthetic skin are described.